Diversity analysis of Philippine bananas using simple sequence repeats markers - Dacumus, Claudette N.; Patena, Lilian F.; Barba, Ramon C. (2011)
Simple Sequence Repeats (SSRs) were used to determine the genetic variability and relationships among sixty-one genotypes of Philippine bananas. Ten out of twelve primer pairs tested were found to be polymorphic and generated 43 alleles ranging from 3 to 13 alleles per primer. Seven out of the ten primers gave unique bands for some of the genotypes tested showing their potential use in cultivar identification and fingerprinting. The resolving power of molecular markers measured as the Polymorphism Information Content (PIC) ranged from 0.68 to 0.94. Cluster analysis at the 83.1% similarity divided the dendrogram into 11 clusters with several outliers indicating a wide genetic variation existing within the different Musa genotypes. Cluster analysis separated the genotypes of Musa acuminata from other genotypes with A and B genomes although no cohesive clustering among different groups, (i.e. diploids, triploids, and tetraploids) was observed.
Keywords: Banana--Genetics